Beginning Zend Framework - Padilla, Armando (Apress : Imprint: Apress, 2009)
The Zend Framework is one of today's most popular PHP-based web application development frameworks. Beginning Zend Framework is a beginner's guide to learning and using the Zend Framework. It covers everything from the installation to the various features of the framework to get the reader up and running quickly.